2022
DOI: 10.1080/08897077.2021.1941517
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Cannabis-Related Attitudes and Behaviors among Cannabis-Using Adolescent and Young Adult Outpatients following Medical Cannabis Legalization in Massachusetts

Abstract: Background: Among youth already using cannabis, legalization of medical cannabis may influence cannabis-related attitudes and behaviors, including increasing access through use of someone else's medical cannabis (diversion). Objective: To examine cannabis-related attitudes and behaviors (including diverted cannabis use) in cannabis-using youth in the four years following medical cannabis legalization. Additionally, we investigated characteristics of youth who used vs. did not use diverted medical cannabis. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…There is, however, some evidence suggesting that medical marijuana legislation and legalization of recreational cannabis use in several states of the USA has increased the use of cannabis (and emergencies related to the use of cannabis 31 ) and may increase the prevalence of cannabinoid use disorders. 23 , 32 Therefore, the possibility to prescribe cannabinoids under certain conditions at the expense of the statutory health insurances in Germany as of March 2017 22 and the long-standing political debates in Germany about legalization/decriminalization of recreational cannabis use may have affected the attitude of the general population towards the use of cannabinoids and indirectly increased the use of cannabinoids in Germany. Secondly, synthetic cannabinoids and illicit cannabinoid preparations derived from special breedings and/or genetically engineered Cannabis sativa plants with higher and occasionally extremely high content of THC are increasingly used in Germany in the last decades.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is, however, some evidence suggesting that medical marijuana legislation and legalization of recreational cannabis use in several states of the USA has increased the use of cannabis (and emergencies related to the use of cannabis 31 ) and may increase the prevalence of cannabinoid use disorders. 23 , 32 Therefore, the possibility to prescribe cannabinoids under certain conditions at the expense of the statutory health insurances in Germany as of March 2017 22 and the long-standing political debates in Germany about legalization/decriminalization of recreational cannabis use may have affected the attitude of the general population towards the use of cannabinoids and indirectly increased the use of cannabinoids in Germany. Secondly, synthetic cannabinoids and illicit cannabinoid preparations derived from special breedings and/or genetically engineered Cannabis sativa plants with higher and occasionally extremely high content of THC are increasingly used in Germany in the last decades.…”
Section: Discussionmentioning
confidence: 99%
“… 16–21 Moreover, the respective legal frameworks have changed significantly (e.g. approval of medical cannabis 22 and legalization of cannabinoid use 19 , 23 ). In addition, potentially more harmful cannabinoid preparations (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Although the study focused on Israeli law and the perceptions of the Israeli public, it is relevant to many other countries. The review of the literature shows that medical cannabis is diverted in many countries, including the US (Nussbaum et al, 2015; O’Connell et al, 2022) and South America countries (Fairman, 2016). However, the external validity of the study is limited, since its findings cannot be generalized to countries where the use of cannabis has been legalized or where medical cannabis is not authorized.…”
Section: Discussionmentioning
confidence: 99%
“…O’Connell et al (2022) found that in 2016, 44% of cannabis-using youths (age 13–24) in Boston reported using diverted medical cannabis, compаred to 14.9% in 2013. Tandowski et al (2019) found that of 1387 people that use cannabis in Israel, 70% reported using diverted medical cannabis at least once in their lifetime, but only 30% reported using 6 times or more.…”
Section: Introductionmentioning
confidence: 99%